THE IMPORTANCE OF EARLY MOBILIZATION IN ICU PATIENTS: EFFECTS ON RESPIRATORY FUNCTION AND LENGTH OF STAY - Martins, Poliana Barros (Revista Sistemática, 2022)
Early mobilization combined with respiratory physiotherapy in mechanically ventilated ICU patients is a key intervention that enhances respiratory muscle performance, accelerates weaning from mechanical ventilation, and reduces ICU and hospital length of stay. This experimental approach addresses ICU-acquired weakness and respiratory dysfunction caused by immobility and systemic inflammation. Safety protocols, individualized rehabilitation plans, and multidisciplinary teamwork are essential for effective implementation. The intervention also yields significant cost savings, easing hospital resource burdens. This review highlights the clinical, functional, and economic benefits of early mobilization with respiratory physiotherapy in critically ill patients and underscores the vital role of physiotherapists in multidisciplinary ICU care.